Social and health determinants of gender differences in disability amongst older adults in South Africa - Nancy Phaswana-Mafuya; Karl Peltzer; Shandir Ramlagan; Witness Chirinda; Zamakayise Kose (AOSIS, 2013)
There has been an unprecedented increase in population ageing resulting in the increase in prevalence of various health conditions, including disability and associated risk factors. This study aimed to investigate the prevalence and predictors of functional status and disability amongst older South Africans. Little is known about disability amongst older South Africans because most previous health research has focused on younger individuals and infectious diseases. We conducted a national population-based cross-sectional study with a sample of 3840 subjects aged 50 years or older in South Africa. Multivariable regression analysis was performed in order to assess the association of social factors, health variables and functional disability. Overall, 37.2% of the respondents had moderate or severe and/or very severe functional disability, this being higher amongst women. The highest disability was found for the mobility, cognition and participation domains. In all domains, except for the self-care domain, women had a higher disability prevalence. Multivariable analysis amongst men revealed that older age, having some or primary education, being from Indian or Asian race, having chronic conditions, physical inactivity and a lower quality of life were associated with functional disability. Amongst women, older age, as well as having chronic conditions and a lower quality of life, were associated with functional disability. This study has implications for health-sector strategic plans aimed at preventing disabilities, ensuring access to curative and rehabilitative care. This study forms an evidence base upon which future policies and health care management systems can be based. Daar was 'n ongekende toename in bevolkingsveroudering, wat 'n toename in die voorkoms van verskeie gesondheidstoestande tot gevolg gehad het, insluitende gestremdheid en gepaardgaande faktore. Die studie was daarop gemik om die voorkoms en voorspelbaarheid van die funksionele status en gestremdheid onder ouer Suid-Afrikaners te ondersoek. Daar is min bekennis oor gestremdheid onder ouer Suid-Afrikaners omdat vorige gesondheidsnavorsing meestal op jonger individue en oordraagbare siektes ingestel was. Ons het 'n nasionale bevokings-gebaseerde kruis-seksionele ondersoek uitgevoer op 'n studiemonster van 3840 Suid-Afrikaners, 50-jaar en ouer. Om die verband tussen sosiale faktore, gesondheidsveranderlikes en funksionele gestremdheid te bepaal, is veelvuldig veranderlike regressie-analise uitgevoer. In die algemeen het 37.2% van die respondente matig of ernstige funksionele gestremdheid ervaar wat hoer was onder vroue. Die hoogste vorm van gestremdheid was op die gebiede van beweeglikehid, waarneming en deelname. Die voorkoms van gestremdheid was op alle gebiede hoër in vroue, behalwe op die gebied van selfsorg. Multi-veranderlike ontledings onder mans het getoon dat funksionele gestremdheid geassosieer word met ouderdom, met 'n mate van primêre onderwys, met die Indiese of Asiatiese bevolkingsgroep, en met diegene wat ly aan kroniese toestande (beroerte, slaapprobleme snags), fisiese onaktiwiteit en 'n laer lewenskwaliteit. Die studie het implikasies vir strategiese planne in die gesondheidsektor wat daarop gemik is om gestremdheid te voorkom en om toegang tot genesende en rehabiliterende sorg te verseker. Hierdie studie verskaf 'n grondslag van bewyse waarop beleid- en gesondheidsorg-bestuurstelsels in die toekoms gebaseer kan word.